Metode Bercerita untuk Meningkatan Perilaku Patuh Pada Anak Usia Dini - Lusinta Rehna Ginting (unprimdn.ac.id, 2024)
This study aims to improve obedient behavior in early childhood by applying the storytelling method at PAUD Al-Ihmy Medan. The research method used is Classroom Action Research (PTK) with a quantitative descriptive approach. The subjects of this study were 20 early childhood. Data collection techniques were carried out through observation sheets of children's obedient behavior before and after applying the storytelling method. The results showed that storytelling significantly improved children's obedient behavior in each cycle. At the pre-cycle stage, children's obedience was at an average of 57.24% (less category). After applying the storytelling method in cycle I, the level of compliance increased to 63.89% (sufficient category). A more significant increase occurred in cycle II, where the average obedient behavior reached 78.88% (good category). These results show that the storytelling method is effective in instilling obedience values in early childhood. Thus, storytelling can be an innovative learning strategy to shape children's characters early on.